Colorectal cancer—global burden, trends, and geographical variations. Issue 5 (13th February 2017) - Douaiher, Jeffrey; Ravipati, Advaitaa; Grams, Benjamin; Chowdhury, Sanjib; Alatise, Olusegun; Are, Chandrakanth
Abstract : BACKGROUND: The aim of this study is to describe the trends and variations in the global burden of colorectal cancer (CRC). METHODS: Data (2012‐2030) relating to CRC was extracted from GLOBOCAN 2012 database and analyzed. RESULTS: The results of our study demonstrate a rising global burden of colorectal cancer which persists until the year 2035 and likely beyond. The rise in the global burden is not uniform with significant variations influenced by geographic location, socio‐economic status, age, and gender. Although the EURO region has the highest burden, Asia as a continent continues to bear the heaviest brunt of the disease. Although the burden of disease is higher in more developed regions, mortality is considerably higher in less developed regions and this gap widens over the next two decades. The disease predominantly affects the male gender across all regions of the world. Age has a complex relation with the burden of CRC and is affected by the cross‐influences relating to socio‐economic status. CONCLUSIONS: The results of our study demonstrate a rising global burden of CRC with some unique variations. Knowledge of this data can increase awareness and help strategic targeting of efforts and resources.